Bycatch Analyses of Pot Operated In Coral Reef Waters of Seribu Islands - Dahri Iskandar (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2011)
The objective of this research was to investigate bycatch of pot operated by fishermen in Seribu Island waters. The research was carried out by common pot using by fishermen for catching reef fishes. Pots used in this experiment was made from bamboo with size of length x width x depth : 66 cm x 51 cm x 20 cm. During experiment bamboo pots were operated in single pot setting in depth range of 0,5 m to 3 m. Result of the experiment indicated that catch of pot per trip ranged from 3,7 to 8,9 fishes per pot. Dominant bycatch came from Famili Pomacentridae with total amount 201 fishes or 30, 78% of total catch. Proportion of bycatch was relatively higher than target species with proportion 58% : 42%. Keywords: bycatch, pot, reef, reef fishes, Seribu island